Conservatism - "O' Sullivan, Noel" (London, 1983)
one of the most eloquent and even moving evocations of the conservative tradition in Western politics, philosophy and culture I have ever read$1! =(Bthe ideal primer for those who are new to conservative ideas s
Keywords: Conservatism